Electronic Commerce: Factors Involved in its Adoption from a Bibliometric Analysis - Villa, Eliana; Ruiz, Luis; Valencia, Alejandro; Picón, Edgar (Journal of theoretical and applied electronic commerce research, 2018)
This article presents findings of a study that aimed to identify key factors in the adoption of e-commerce. The study involved a bibliometric analysis of statistical information from 408 scientific publications related to the theme, registered in the Scopus database, through a structured search equation. The collected records were used to calculate bibliometric indicators of quantity, quality and structure. Additionally, an analysis of increasing, decreasing, and emerging thematics was carried out to identify the topics of greatest interest on this subject. Findings indicate that this is a prolific research field, in which the fastest growing topic is the study of e-commerce adoption in small and medium sized enterprises in emerging economies. The analysis also revealed the current use of new models to evaluate adoption factors. That is the case of the Technology Organization Environment Framework used as an alternative to the Technology Acceptance Model-which remains the most widely used. Likewise, Structural Equation Analysis was found to be one of the most frequently used options for statistical analysis in the publications studied. A research agenda intending to contribute with directions for further research in the area is presented at the end of the article.